PENGGUNAAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN AKTIVITAS BELAJAR SENI BUDAYA PADA PESERTA DIDIK KELAS X AP B2 SMK N 3 DENPASAR - I Gusti Agung Ayu Tirta Triratna; I Made Sujana (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Classroom Action Research (PTK) aims to increase cultural arts learning activities in class X AP B2 students of SMK N 3 Denpasar by using Google Sites as learning media. The data collection techniques used were observation of the implementation of the action and the results achieved, and a questionnaire to determine the response to the use of Google Sites learning media. While the data analysis technique used is descriptive qualitative analysis of data from observation of student learning activities with a Ratting scale and questionnaire data using a Guttman scale. The results showed that the use of Google Sites learning media can increase the cultural arts learning activities of students in class X AP B2 SMK Negeri 3 Denpasar. This can be seen from the increase in the average percentage of students' learning activities. In cycle I, the average student learning activity was 47,75%, while in the average percentage of student learning activities in cycle II it was 83.375%, an increase of 35,625%. The category of data analysis of the observation results of cycle II is "Good" because it is in the range of 76-100%.